Back Cover: Homotropic Allosterism: In‐Depth Structural Analysis of the Gas‐Phase Noncovalent Complexes Associating a Double‐Cavity Cucurbit[n]uril‐Type Host and Size‐Selected Protonated Amino Compounds (ChemPlusChem 9/2013). Issue 9 (8th September 2013) - Lemaur, Vincent; Carroy, Glenn; Poussigue, Frédéric; Chirot, Fabien; De Winter, Julien; Isaacs, Lyle; Dugourd, Philippe; Cornil, Jérôme; Gerbaux, Pascal
<x xml:space="preserve">Abstract</x> The back cover picture shows how a combination of experimental and theoretical tools proves attractive for the study of noncovalent interactions between a double‐cavity cucurbit[n]uril‐type receptor and size‐selected guest molecules. In their Full Paper on page 959 ff., P. Gerbaux and co‐workers describe that ternary complexes are smoothly transferred from aqueous solutions to the gas phase upon electrospray ionization. State‐of‐the‐art methods based on mass spectrometry associated with computational chemistry demonstrate the conservation of the condensed‐phase structure during the transfer.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>